Synthesis, Characterization and Thermal Properties of Some New Azopolyimides - Logesh, G.; Rajendiran, T.V. (Asian Journal of Chemistry, 2012)
A new class of aromatic azopolyimides were synthesized from aromatic diamine with 3,3',4,4'- azobenzenetetracarboxlic dianhydride. The synthesis involved the reaction of the dianhydride with respective diamine to yield an intermediate, soluble, open chain precursor polymer of polyamic acid, which on further cyclodehydration by solution, chemical and thermal imidization method yielded the less soluble, high viscosity, high stability, heat resistant or high temperature polyimides. All these polyimides were characterized by UV and IR. Viscosity, solubility, stability and thermal properties of these polymers were also studied.